2019
DOI: 10.1093/mnras/stz965
|View full text |Cite
|
Sign up to set email alerts
|

Orbital relaxation and excitation of planets tidally interacting with white dwarfs

Abstract: Observational evidence of white dwarf planetary systems is dominated by the remains of exo-asteroids through accreted metals, debris discs, and orbiting planetesimals. However, exo-planets in these systems play crucial roles as perturbing agents, and can themselves be perturbed close to the white dwarf Roche radius. Here, we illustrate a procedure for computing the tidal interaction between a white dwarf and a near-spherical solid planet. This method determines the planet's inward and/or outward drift, and whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 159 publications
(169 reference statements)
0
29
0
Order By: Relevance
“…where the magnetic field strength is given by B⋆ and the vertically-averaged electrical conductivity in the white dwarf atmosphere is given by γ⋆ . All notations are consistent with those in Veras et al (2019b).…”
Section: Lorentz Driftmentioning
confidence: 74%
See 3 more Smart Citations
“…where the magnetic field strength is given by B⋆ and the vertically-averaged electrical conductivity in the white dwarf atmosphere is given by γ⋆ . All notations are consistent with those in Veras et al (2019b).…”
Section: Lorentz Driftmentioning
confidence: 74%
“…Surviving planets may alter their orbits in non-obvious ways due to tides alone (Veras et al 2019b), and especially now when coupled with an electromagnetic force. Nevertheless, conveniently we found that the planets do not move outward enough to exceed acrit.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Capture into spin-orbit resonances and psuedo-synchronous rotation states cannot be accurately realised with such models (Makarov & Efroimsky 2013;Noyelles et al 2014). Instead, the direction of the net tidally-induced migration is chaotic with respect to the multi-dimensional parameter space (Veras et al 2019), and hence very well might produce gaps like the one seen here.…”
Section: Tidesmentioning
confidence: 89%